Case study: company analysis Fid Food / Balqis Abdul Somat … [et al.] - Abdul Somat, Balqis; Mazlan, Iffah Syasya Radhiah; Mat Ripin, Muhamad Adam Aiman; Abdul Jalil, Nur Farah Izlyn; Mohd Nasir, Nur Nisyrina (2022)
This case study report is about the business details based on the interview that has been made by our group with Fid Food which is a small and medium-sized enterprise. Fid Food is located in Arau, Perlis. Based on the information that we have received from the owner of Fid Food, Madam Rafidah Ali, we can analyze the strengths and weaknesses from this business. Besides, we can describe more about these business strategies by using Business Model Canvas (BMC). Other than that, we need to analyze the major problems about the products, operation, marketing and other business aspects in Fid Food. Based on the problems that we have figured out, we should come up with possible solutions by innovating the current products or services of Fid Food.